Investigating the relationships between unfavourable habitual sleep and metabolomic traits: evidence from multicohort multivariable regression and Mendelian randomization analyses - Bos, MM; Goulding, NJ; Lee, MA; Hofman, A; Bot, M; Pool, R; Vijfhuizen, LS; Zhang, X; Li, C; Mustafa, R; Neville, M; Li-Gao, R; et al. (BMC, 2021)
Background: Sleep traits are associated with cardiometabolic disease risk, with evidence from Mendelian randomization (MR) suggesting that insomnia symptoms and shorter sleep duration increase coronary artery disease risk. We combined adjusted multivariable regression (AMV) and MR analyses of phenotypes of unfavourable sleep on 113 metabolomic traits to investigate possible biochemical mechanisms linking sleep to cardiovascular disease.